The effect of substitutional doping of Yb2+ on structural, electronic, and optical properties of CsCaX3 (X: Cl, Br, I) phosphors: a first-principles study. (18th November 2021) - Khan, Rashid; Ur Rahman, Kaleem; Zhang, Qingmin; Rahman, Altaf Ur; Azam, Sikander; Dahshan, Alaa
Abstract: Using first-principles calculations, the effects of Yb 2+ substitutional doping on structural, electronic, and optical properties of a series of perovskite compounds CsCa X 3 ( X : Cl, Br, I), have been investigated. We employed generalized gradient approximation (GGA) and HSE hybrid functional to study the electronic and optical properties. A series of pristine CsCa X 3 ( X : Cl, Br, I) is characterized as a non-magnetic insulator with indirect bandgap perovskite materials. These phosphor materials are suitable candidates for doping with lanthanide series elements to tune their electronic bandgaps according to our requirements because of their wide bandgaps. The calculated electronic bandgaps of CsCa X 3 ( X : Cl, Br, I) are 3.7 eV (GGA) and 4.5 eV (HSE) for CsCaI3, 4.5 eV (GGA) and 5.3 eV (HSE) for CsCaBr3, and 5.4 eV (GGA) and 6.4 eV (HSE) for CsCaCl3 . According to formation energies, the Yb 2+ doped at the Ca-site is thermodynamically more stable as compared to all possible atomic sites. The electronic band structures show that the Yb 2+ doping induces defective states within the bandgaps of pristine CsCa X 3 ( X : Cl, Br, I). As a result, the Yb 2+ doped CsCa X 3 ( X : Cl, Br, I) become the direct bandgap semiconductors. The defective states above the valence band maximum are produced due to the f -orbital of the Yb atom. The impurity states near the conduction band minimum are induced due to the major contribution of d -orbital of the Yb atom and the minor contribution of s -orbital of the Cs atom. The real and imaginary parts of the dielectric function, optical reflectivity, electron energy loss spectrum, extinction coefficient, and refractive index of pristine and Yb 2+ doped CsCa X 3 ( X : Cl, Br, I) were studied. The optical dispersion results of dielectric susceptibility closely match their relevant electronic structure and align with previously reported theoretical and experimental data. We conclude that the Yb 2+ doped CsCa X 3 ( X : Cl, Br, I) are appealing candidates for optoelectronic devices.